Hypersensitivity Induced by Activation of Spinal Cord PAR2 Receptors Is Partially Mediated by TRPV1 Receptors - Mrozkova, Petra; Spicarova, Diana; Palecek, Jiri (PloS one, 2016)
Protease-activated receptors 2 (PAR2) and transient receptor potential vanilloid 1 (TRPV1) receptors in the peripheral nerve endings are implicated in the development of increased sensitivity to mechanical and thermal stimuli, especially during inflammatory states. Both PAR2 and TRPV1 receptors are co-expressed in nociceptive dorsal root ganglion (DRG) neurons on their peripheral endings and also on presynaptic endings in the spinal cord dorsal horn. However, the modulation of nociceptive synaptic transmission in the superficial dorsal horn after activation of PAR2 and their functional coupling with TRPV1 is not clear. To investigate the role of spinal PAR2 activation on nociceptive modulation, intrathecal drug application was used in behavioural experiments and patch-clamp recordings of spontaneous, miniature and dorsal root stimulation-evoked excitatory postsynaptic currents (sEPSCs, mEPSCs, eEPSCs) were performed on superficial dorsal horn neurons in acute rat spinal cord slices. Intrathecal application of PAR2 activating peptide SLIGKV-NH2 induced thermal hyperalgesia, which was prevented by pretreatment with TRPV1 antagonist SB 366791 and was reduced by protein kinases inhibitor staurosporine. Patch-clamp experiments revealed robust decrease of mEPSC frequency (62.8 ± 4.9%), increase of sEPSC frequency (127.0 ± 5.9%) and eEPSC amplitude (126.9 ± 12.0%) in dorsal horn neurons after acute SLIGKV-NH2 application. All these EPSC changes, induced by PAR2 activation, were prevented by SB 366791 and staurosporine pretreatment. Our results demonstrate an important role of spinal PAR2 receptors in modulation of nociceptive transmission in the spinal cord dorsal horn at least partially mediated by activation of presynaptic TRPV1 receptors. The functional coupling between the PAR2 and TRPV1 receptors on the central branches of DRG neurons may be important especially during different pathological states when it may enhance pain perception.
Keywords: Behavior, Animal; buňky zadních rohů míšních; Hyperalgesia; metoda terčíkového zámku; In Vitro Techniques; Rats; Oligopeptides; nervový přenos; Protein Kinase Inhibitors; receptor PAR-2; Posterior Horn Cells; Hypersensitivity; TRPV Cation Channels; alergie; Staurosporine; Rats, Wistar; mužské pohlaví; oligopeptidy; techniky in vitro; Patch-Clamp Techniques; staurosporin; krysa rodu Rattus; Excitatory Postsynaptic Potentials; excitační postsynaptické potenciály; Receptor, PAR-2; zvířata; kationtové kanály TRPV; Cinnamates; Synaptic Transmission; hyperalgezie; chování zvířat; Spinal Cord; anilidy; inhibitory proteinkinas; potkani Wistar; cinnamáty; mícha; Anilides; Male; Animals